Pengaruh Pendapatan Dan Lingkungan Sosial Terhadap Minat Menabung Mahasiswa Pada Bank BRI - Ruhamak, Muhammad Dian; Dewandaru, Bothy; Andriani, Nabila; Zalviana, Ridha; Listiyaningrum, Isro’in; Cahyani, Risma Gesang Ayu; Jorumana, Deni Umbu Siwa (Program Studi Ekonomi Pembangunan, Fakultas Ekonomi, Universitas Warmadewa, 2024)
This research aims to analyze how much income and social environment influence the interest in saving among students in regular morning classes at the Faculty of Economics and Business, Kadiri University. This article's quantitative research uses primary data obtained through observation, interviews, and distributing questionnaires. The sample used in this research was 50 respondents. The data analysis techniques used are the Validity Test and Reliability Test, Multiple Linear Regression Analysis Test, and Hypothesis Test (T-test, F Test, and Determination Coefficient Test (R2)). Based on the test results, it was found that the Income variable had a significant influence on the Interest in Saving variable, the Social Environment variable had a significant influence on the Interest in Saving variable, the Income variable and the Social Environment variable had a significant influence on the Interest in Saving variable. The Income and Social Environment variables influence 36.3% of the Interest in Saving variable, while other factors outside this research influence the remaining 67.7%.